2023
DOI: 10.1021/acsanm.2c05557
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Branched Gold Nanostar-Based Lateral-Flow Immunoassay for Detection of Yersinia pestis

Abstract: Over the past few decades, colorimetric paper-based lateral flow immunoassay (LFIA) has emerged as a versatile analytical tool for rapid point-of-care detection of infectious diseases with high simplicity and flexibility. The LFIA sensitivity is based on color visualization of the antibody-labeled nanoparticles bound with the target analytes at the test line. Therefore, the nanoparticle design is crucial for LFIA sensitivity. The traditional LFIA is based on spherical gold nanoparticles, which usually suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The red-shifting of the plasmon peak is consistent with our previous studies for antibody conjugation of gold nanostars. 12 Figure 4a shows the schematic representation of the colorimetric LFIA platform. Figure 4b shows the color brightness of GNC-2 and 35 nm GNSP at the same concentration (60 pM), indicating that GNC-2 has the highest color brightness than GNSP.…”
Section: Sers Enhancement Study Of Gncmentioning
confidence: 99%
See 3 more Smart Citations
“…The red-shifting of the plasmon peak is consistent with our previous studies for antibody conjugation of gold nanostars. 12 Figure 4a shows the schematic representation of the colorimetric LFIA platform. Figure 4b shows the color brightness of GNC-2 and 35 nm GNSP at the same concentration (60 pM), indicating that GNC-2 has the highest color brightness than GNSP.…”
Section: Sers Enhancement Study Of Gncmentioning
confidence: 99%
“…12−16 For instance, we have recently shown that high aspect-ratio, sharp-branched gold nanostars possess higher optical contrast over conventional gold nanospheres, which improved the colorimetric LFIA sensitivity. 12 Therefore, further nanoparticle optimization can improve the visual color brightness and increase the sensitivity of the LFIA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final concentration of the CTAB-capped GNSs was calculated to be 2 pmol L −1 by following our previously reported procedure. 58 As the GNSs were centrifuged and dis-persed in water, we believe that the amount of CTAB in the GNS solution was negligible.…”
Section: Synthesis Of Gnsmentioning
confidence: 99%